2011
DOI: 10.2174/187152811796117735
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Utility of Kidney Injury Molecule 1 in the Prediction, Diagnosis and Prognosis of Acute Kidney Injury: A Systematic Review

Abstract: Kim-1 is a potential novel urinary biomarker in the early detection of AKI within 24 hours after kidney insult. It might be especially beneficial in the diagnosis of ischemic ATN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
65
0
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(70 citation statements)
references
References 31 publications
0
65
0
5
Order By: Relevance
“…[22,23]. Bupropion does not decrease significantly TNF-α levels (p=0.06) despite identifying a tendency of lowering, but it was necessary to conserve the renal function of the right kidney (Table 2).…”
Section: Discussionmentioning
confidence: 98%
“…[22,23]. Bupropion does not decrease significantly TNF-α levels (p=0.06) despite identifying a tendency of lowering, but it was necessary to conserve the renal function of the right kidney (Table 2).…”
Section: Discussionmentioning
confidence: 98%
“…Huang et al (16) found that the levels of the uKIM-1 are the highest in patients with acute ischemic tubular necrosis. Detected values of uKIM-1 among patients vary widely, and are influenced by the time.…”
Section: Discussionmentioning
confidence: 99%
“…Two large studies have shown that KIM-1 is an effective new urinary biomarker for the diagnosis of AKI in the first 24 h after kidney injury, especially for the diagnosis of ischemic AKI (15,16). Askenazi et al (6) examined the different urinary biomarkers as predictors of AKI and mortality in very-low-birthweight infants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…20 In two recently published systematic reviews, it has been reported that KIM-1 was an effective and reliable urinary biomarker for diagnosing AKI within 24 h of renal injury. 21,22 Clinical studies have demonstrated the excessive tubular production of KIM-1 in FSGS, IgA nephropathy, and MPGN. Moreover, a linear and proportional correlation was revealed between increased KIM-1 levels, proteinuria, development of tubular damage, and interstitial fibrosis secondary to proteinuria.…”
Section: Discussionmentioning
confidence: 99%